Visual guidebooks: documenting a personal thinking language. Issue 1 (2nd January 2017) - Shambaugh, Neal; Beacham, Cindy
Abstract: A personal thinking language consists of verbal and visual means to transform ideas to action in social and work settings. This verbal and visual interaction of images and language is influenced by one's personal history, cultural expectations and professional practices. The article first compares a personal thinking language to other languages (e.g. design, private languages), cites its benefits and identifies its features. The article describes how a visual guidebook can be used as an educational task to document a student's personal thinking language. Recommendations for implementing a visual guidebook are provided for academic and professional settings.